Seroprevalence of diphtheria and pertussis immunoglobulin G among children with pneumonia in Ji'nan, China - Qinghong Meng; Lijun Li; Wei Shi; Qing Wang; Mingjie Ding; Yanqin Liu; Xiang Ma; Kaihu Yao (BMC, 2018)
Abstract Background Vaccination is still one of the most important methods to control and prevent childhood infections including diphtheria and pertussis. This study evaluated the level of diphtheria (DT) and pertussis (PT)-related antibodies among children with pneumonia in Ji'nan, China. Methods A total of 484 sera of children from 1 day to 13 years of age were collected from 2014 to 2015 in Ji'nan. Children with recent history of pertussis were excluded from this study. Anti-DT and PT IgG concentrations were measured by ELISA (Euroimmun, Lübeck, Germany). Results Of the 484 subjects tested, the overall positivity rate of anti-DT IgG (≥0.1 IU/ml) was 48.97%, and the highest positivity rate of anti-DT IgG (68.55%) and proportion with long term protection (23.27%) were observed in children aged 6 m- < 3 y. For anti-PT IgG, 334 subjects (69.01%) had anti-PT IgG levels below the lower limit of detection (5 IU/ml). Even with detectable anti-PT antibodies, the majority (115/150, 76.67%) of them had antibody levels of 5- < 40 IU/ml. The highest proportion of subjects with detectable anti-PT IgG (≥5 IU/ml) was observed in children aged < 6 m (44.36%), then the proportion continually decreased to 15.0% at 3 y- < 6 y (χ 2  = 24.05, p < 0.0001). The highest positivity rate (≥40 IU/ml) was only 8.27% in children aged < 6 m. Subjects with an anti-PT IgG ≥100 IU/ml were observed in all the groups and there were no significant differences in the proportions of subjects with a level ≥ 100 IU/ml among these age groups (χ 2  = 2.572, p = 0.4624). A total of 5 subjects had anti-PT IgG ≥100 IU/ml (≥1 years post pertussis vaccination) which was considered to be indicative of a recent pertussis infection. Conclusions We demonstrated low antibody levels and protection against pertussis in our study population. The anti-PT IgG maintained a low level throughout all age groups, and even no immune responses were observed after the basic immunization and booster. Our study supported the need to reevaluate the immune response of DTP vaccine which was used in Shandong province after 2010.